Pharmaceutical emulsion with increased viscosity for local use of glucocorticosteroids in the esophagus - Alicja Bieńkowska; Iga Osińska; Joanna Nowosielska; Arkadiusz Leloch; Krzysztof Gawrychowski; Aleksandra Banaszkiewicz; Maciej Małecki (Polish Pharmaceutical Society, 2020)
Background The pharmaceutical recipe allows to improve formulations for special medical indications. In the medical environment, the appeal for new pharmaceutical forms for already known active substances is evident. The treatment of patients with eosinophilic esophagitis is a significant difficulty. New formulations for glucocorticosteroids are searching. An interesting solution may be pharmaceutical formulations with increased viscosity that allow to higher efficiency of local adsorption for an anti-inflammatory active substances, than currently available drugs. Aim of the study The aim of the study was to develop a pharmaceutical formulation for the local use of glucocorticosteroids in patients with eosinophilic esophagitis. It was assumed to obtain a preparation with increased viscosity and to carry out an assessment of physicochemical properties. Materials and methods The formulation was obtained at the Department of Applied Pharmacy. The recipe standards were followed. An emulsive, liquid formulation (o/w) containing polysaccharide and oilly excipitients was obtained. Budesonidum was chosen as the active substance. The stability and persistence of the developed formulation stored at room temperature and at 4°C were evaluated. A cylinder, pendulum, dose capacity, coating tests were carried out. The pH, viscosity and osmolarity were assessed. Results A pharmaceutical formulation (Steroid) with increased adhesive properties was obtained. The research showed that the developed formulation allows to a significant increase in the adhesive properties of Budesonidum. The viscosity of the Steroid formulation/Budesonidum system has been shown to be about 25 times higher than that of pure Budesonidum preparation, when the coating time is about 11 times longer for the Steroid formulation/Budesonidum. The study also showed that the obtained emulsion was stable at 4°C for up to 31 days. Conclusions The Steroid formulation is emulsion which increases the adhesive properties of a steroidal anti-inflammatory drug Budesonidum. It is possible to administer the Steroid formulation with Budesonidum locally to patients with eosinophilic esophagitis. The present work proves that the pharmaceutical recipe through new viscous formulations can be helpful in increasing the therapeutic availability of well know active substances.